Energy allocation during the maturation of adults in a long-lived insect: implications for dispersal and reproduction. Issue 5 (9th July 2015) - David, G.; Giffard, B.; van Halder, I.; Piou, D.; Jactel, H.
Abstract Energy allocation strategies have been widely documented in insects and were formalized in the context of the reproduction process by the terms 'capital breeder' and 'income breeder'. We propose here the extension of this framework to dispersal ability, with the concepts of 'capital disperser' and 'income disperser', and explore the trade-off in resource allocation between dispersal and reproduction. We hypothesized that flight capacity was sex-dependent, due to a trade-off in energy allocation between dispersal and egg production in females. We used Monochamus galloprovincialis as model organism, a long-lived beetle which is the European vector of the pine wood nematode. We estimated the flight capacity with a flight mill and used the number of mature eggs as a proxy for the investment in reproduction. We used the ratio between dry weights of the thorax and the abdomen to investigate the trade-off. The probability of flying increased with the adult weight at emergence, but was not dependent on insect age or sex. Flight distance increased with age in individuals but did not differ between sexes. It was also positively associated with energy allocation to thorax reserves, which increased with age. In females, the abdomen weight and the number of eggs also increase with age with no negative effect on flight capacity, indicating a lack of trade-off. This long-lived beetle has a complex strategy of energy allocation, being a 'capital disperser' in terms of flight ability, an 'income disperser' in terms of flight performance and an 'income breeder' in terms of egg production.